2020
DOI: 10.1177/1049732320916460
|View full text |Cite
|
Sign up to set email alerts
|

The Wicked Problem of Stigma for Youth Living With Anxiety

Abstract: Anxiety disorders typically emerge in childhood and, if left untreated, can lead to poor health and social outcomes into adulthood. Stigma contributes to the burden of mental illness in youth. Mental health stigma has been conceptualized as a wicked problem and efforts to address this complexity require a greater understanding of how stigma operates in the lives of youth. Fifty-eight youth in Manitoba, Canada aged 10 to 22 years and living with anxiety took part in the study. Data collection involved in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This finding appears consistent with Biddle and colleagues’ (2007) observation that young people may defer help-seeking until prompted by a crisis or external intervention. Adolescents’ concerns about embarrassment, found in this study, also support findings in the wider literature that young people may be put off help-seeking because they anticipate embarrassment and negative or stigmatizing reactions not only from peers but also from mental health professionals (Woodgate et al, 2020; Yap et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…This finding appears consistent with Biddle and colleagues’ (2007) observation that young people may defer help-seeking until prompted by a crisis or external intervention. Adolescents’ concerns about embarrassment, found in this study, also support findings in the wider literature that young people may be put off help-seeking because they anticipate embarrassment and negative or stigmatizing reactions not only from peers but also from mental health professionals (Woodgate et al, 2020; Yap et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The three researchers analyzed ecomaps by their three specific aspects-relationships, social networks, and supports, according to Hartman (1978) and validated by more contemporary researchers (Johnson et al, 2017;Silveira & Neves, 2019;Woodgate et al, 2020), as well as by preconceived codes. Table 1 shows the main categories informed by analyzing the three sources of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This tool offers an interfacial nature, pointing out conflicts to be mediated, bridges to be built, and resources to be sought and mobilized ( Hartman, 1978 ). The ecomaps have been employed to analyze support networks for children, adolescents, and young people, helping to understand relationships in a person’s life and how communication and interaction occur ( Johnson et al, 2017 ; Silveira & Neves, 2019 ; Woodgate et al, 2020 ). In addition, when the same pattern of a diagram is used for data production, comparisons between cases can be established ( Bravington & King, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enacted stigma entails the experience of negative social judgment and discrimination, while felt stigma entails internalized shame associated with having a health condition and fear of experiencing discriminatory acts (Lekas et al, 2011;Scambler, 2004). Health-related stigma is a persistent problem in many communities around the world (Kemp et al, 2019;Sercu & Bracke, 2017;Stangl et al, 2019;Woodgate et al, 2020) and is known to negatively affect the quality of life of people living with stigmatized health conditions (Holzemer et al, 2009;Mosanya et al, 2013;Tsutsumi et al, 2007) and hamper the treatment and management of their disease (Sercu & Bracke, 2017;Stangl et al, 2019). Studies have shown that health-related stigma, particularly felt stigma, can be improved through various stigma reduction strategies and interventions targeted towards people living with stigmatized conditions (Dadun et al, 2019;Lusli et al, 2016;Peters et al, 2016;Rao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%